Revitalizing coastal women’s SMEs in Mandalika SEZ: The moderating role of blue justice - Mohammad Najib Roodhi; Muhammad Mujahid Dakwah; Zefanya Andryan Girsang; Abdurrahman Abdurrahman; Dione Darmansyah Putra Alief; Ahmad Rizki Rizaldi Moerad; Aulia Safira (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
Women-led small and medium enterprises (SMEs) in coastal tourism areas play a crucial role in supporting local economies, yet they continue to face structural constraints in accessing resources, markets, and institutional support. This study examines the effects of human capital, social capital, financial capital, and local wisdom on adaptive capacity and entrepreneurial capability, and their contribution to SMEs revitalization in the Mandalika Special Economic Zone (SEZ). This research adopts an explanatory sequential mixed-method design, integrating a semi-systematic literature review and quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The literature review draws on recent Scopus-indexed journal articles up to 2025 to identify key constructs and theoretical relationships. Quantitative data were collected through a structured questionnaire from 156 coastal women entrepreneurs in the Mandalika SEZ. The findings reveal that human capital, social capital, and local wisdom significantly enhance adaptive capacity. However, adaptive capacity alone does not directly drive SMEs revitalization. Instead, blue justice emerges as a critical factor that directly influences revitalization and strengthens the relationship between adaptive capacity and business outcomes. These findings imply that capacity-building initiatives must be complemented by equitable access to resources, inclusive governance, and fair benefit distribution. Future research should explore longitudinal dynamics and cross-regional comparisons in coastal tourism economies.